Work, family, health, and well-being - Bianchi, Suzanne M.; Casper, Lynne M.; King, Rosalind Berkowitz (Lawrence Erlbaum, 2005)
This work grew out of a conference held in Washington, D.C. in June 2003 on "Workforce/Workplace Mismatch: Work, Family, Health, and Well-Being" sponsored by the National Institute of Health (NIH). The text considers multiple dimensions of health and well-being for workers and their families, children, and communities.